MAKING NORTH SULAWESI PROVINCE TOURISM WEBSITE USING MICROSOFT WORD 2000 - Muhammad Sabar; Damerianta Sahni P, SKom, MMSI Damerianta Sahni P, SKom, MMSI (Jurnal Sistem Informasi, 2001)
Making Tourism Website of North Sulawesi province using Microsoft Word 2000 isan application contains information about the surrounding WWWW North Sulawesi,the state geology, climate, unique wildlife around the North Sulawesi province areprotected, potential tourist attraction of North Sulawesi province are packed in anattractive form . Expected creation of this website can help users in finding additionalpages of information on North Sulawesi province.Using Microsoft Word 2000, this application is the combination of bits of the webpages are pictures, text animations, which are summarized into a single applicationthat is expected in the form of easy to use for anybody and made as attractive aspossible.By simply clicking a button from the menu options the user will immediately get theinformation quickly.